Influence of Boron doping on microcrystalline silicon growth - 李新利 陈永生 杨仕娥 谷锦华 卢景霄 郜小勇 李瑞 焦岳超 高海波 王果 (Chinese physics B, 2011)
Microcrystalline silicon （μc-Si：H） thin films with and without boron doping are deposited using the radio-frequency plasma-enhanced chemical vapour deposition method. The surface roughness evolutions of the silicon thin films are investigated using ex situ spectroscopic ellipsometry and an atomic force microscope. It is shown that the growth exponentβ and the roughness exponent cχ are about 0.369 and 0.95 for the undoped thin film, respectively. Whereas, for the boron-doped μc-Si：H thin film, t3 increases to 0.534 and cχ decreases to 0.46 due to the shadowing effect.